Calorimetric Investigations of a Series of Energetic Polyphosphazenes - Contini, Alessandro E. (Cranfield University, 2008)
Energetic, fluorinated, linear polyphosphazenes are currently under investigation as potential, high-density binders for new, polymer bonded explosive compositions. A series of such polymers was synthesised and the enthalpy of combustion of each member of the series was measured by static bomb calorimetry. This was performed after combusting appropriate secondary thermochemical standards to model the combustion stoichiometry of the heteroatoms nitrogen, fluorine and phosphorus. The water-soluble combustion products were identified and quantified using 19F NMR spectroscopy and Ion Chromatography. Since some of the combustion products are hydrolytically unstable, it was found necessary to stabilise the initial combustion product mixtures by using a buffer solution instead of pure water in the bomb, and then to determine the composition of the stabilised product mixtures in order to obtain meaningful values for the enthalpies of combustion and thence enthalpies of formation. The thermochemical measurements themselves were made with pure water in the bomb. The composition and structures of the various polyphosphazenes were correlated with their energies of combustion and enthalpies of formation. The latter were calculated using the latest CODATA values of enthalpy of formation of the combustion products. The ‘combustion’ of the polyphosphazenes under a nitrogen atmosphere was also investigated with the view to calculating the enthalpies of detonation of each member of the series. Three conference papers which include the results of this work have been published and are included in Appendices C-E.